The Roles of Parent-and-Child Mental Health and Parental Internet Addiction in Adolescent Internet Addiction: Does a Parent-and-Child Gender Match Matter? - Lawrence T. Lam; Lawrence T. Lam (Frontiers Media S.A., 2020)
Objective: This study aimed to investigate the relationship between parental mental health, particularly depression, and Internet addiction (IA) among adolescents taking into consideration adolescent mental health and parental IA as possible mediating factors. Of particular interest was the effect of parent-and-child gender match on these relationships.Materials and Methods: This was a population-based parent-and-child dyad health survey utilizing a random sampling technique. Adolescent IA was measured by the Internet Addiction Test (IAT) designed by Young. The mental health status of the parents was assessed using the Depression, Anxiety, Stress Scale (DASS). Data were analyzed using Structural Equation Model (SEM) techniques with stratification by parent-and-child gender match.Results: One thousand ninety-eight (n = 1,098) parent-and-child dyads were recruited, and useful information was obtained. The mean IAT score was 28.6 (SD = 9.9) for parents and 41.7 (SD = 12.4) for adolescents. Results of the SEM suggested that the effect of parental depression on adolescent IA was mediated through adolescent mental health mainly through adolescent stress (regression weight = 0.33, p < 0.001) and less so through adolescent depression (regression weight = 0.19, p < 0.001) or parental IA (regression weight = 0.13, p < 0.001). Further analysis revealed that these mediating relationships are more significantly manifested in the father-and-son and mother-and-daughter dyads.Conclusions: Result suggested that the relationship between parental mental health and adolescent IA is complex and that adolescent mental health and parental IA also play important roles as mediating factors. These results have direct implications on the treatment and prevention of IA among young people.